Economic development of Polish voivodeships in the years 2010-2014. Application of taxonomic measure of development with entropy weights - Michal Bernard Pietrzak; Adam P. Balcerzak (Institute of Economic Research (IER), 2017)
Implementing policy and forming socioeconomic conditions that support sustainable and equable growth of regions is currently an important objective both at European and national level. Regional development policy is supported by significant resources from European Union funds. As a result, a constant monitoring of the development process at regional level with application of quantitative methods is an important scientific and practical task. Thus, the aim of the article is to assess the level of economic development in Poland at the voivodeships level (NUTS 2). Economic development is considered here as a multiple-criteria phenomenon. In the case of multiple-criteria analysis a common dilemma is attributed to the problem of applying appropriate weights for variables used in the research. Therefore, in order to provide a rating of voivodeships a taxonomic measure of development with entropy weights was applied here. The research was conducted for the years 2010-2014. It was based on the data provided by Central Statistical Office of Poland. The results of the analysis confirm that in spite of a progress obtained by all voivodeships significant disparities between them are still present.
Keywords: O18; P25; C38; 330; entropy weighs; multiple-criteria decision analysis; taxonomic measure of development; regional development